Diasporas in conflict: peace-makers or peace-wreckers? - Smith, Hazel; Stares, Paul B. (United Nations Univ. Press, 2007)
The analytical and conceptual framework -- Diasporas in international conflict / Hazel Smith -- A neglected relationship: diasporas and conflict resolution / Jacob Bercovitch -- Gender, diasporas and post--cold war conflict / Nadje S. Al-Ali -- The case studies -- The Jewish diaspora and the Arab-Palestinian-Israeli conflict / Gabriel Sheffer -- The Palestinian diaspora / Mohammed A. Bamyeh -- The Armenian diaspora and the Karabagh conflict since 1988 / Khachig Tölölyan -- A reluctant diaspora? the case of Colombia / Virginia M. Bouvier -- The Cuban diaspora / Jean Grugel and Henry Kippin -- The Sri Lankan Tamil diaspora: sustaining conflict and pushing for peace / C. Christine Fair -- Kurdish interventions in the Iraq war / Denise Natali -- The mobilized Croatian diaspora: its role in homeland politics and war / Zlatko Skrbis -- African diasporas and post-conflict reconstruction: an Eritrean case study / Khalid Koser -- Political remittance: Cambodian diasporas in conflict and post conflict / Khatharya Um